The role of the cytokines IL-27 and IL-35 in cancer - Avner Friedman; Kang-Ling Liao (Mathematical Biosciences and Engineering)
The cancer-immune interaction is a fast growing field of research in biology, where the goal is to harness the immune system to fight cancer more effectively. In the present paper we review recent work of the interaction between T cells and cancer. CD8$^+$ T cells are activated by IL-27 cytokine and they kill tumor cells. Regulatory T cells produce IL-35 which promotes cancer cells by enhancing angiogenesis, and inhibit CD8$^+$ T cells via TGF-$β$ production. Hence injections of IL-27 and anti-IL-35 are both potentially anti-tumor drugs.The models presented here are based on experimental mouse experiments, and their simulations agree with these experiments. The models are used to suggest effective schedules for drug treatment.